2016
DOI: 10.1161/jaha.116.004138
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA‐188, ‐30a, and ‐30e as Early Biomarkers for Contrast‐Induced Acute Kidney Injury

Abstract: BackgroundContrast‐induced acute kidney injury (CI‐AKI) is typically defined by an increase in serum creatinine after intravascular administration of contrast medium. Because creatinine is an unreliable indicator of acute changes in kidney function, we assessed whether circulating microRNAs (miRNAs) could serve as biomarkers for early detection of CI‐AKI.Methods and ResultsUsing a rat model of CI‐AKI, we first evaluated the miRNA profile of rat plasma and kidney. Three miRNA species with >1.5‐fold increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 30 publications
4
51
1
Order By: Relevance
“…From our small-RNAseq results, we identified miRNAs that showed significant concentration changes in patients when compared with non-DN controls (for patients with overt DN) or when compared with their previous non-MA urine collection cycle (for patients with IMA or PMA). Many of these miRNAs have been previously associated with kidney function, and have roles in the pathophysiology of diabetes 23 , 24 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , ...…”
Section: Discussionmentioning
confidence: 99%
“…From our small-RNAseq results, we identified miRNAs that showed significant concentration changes in patients when compared with non-DN controls (for patients with overt DN) or when compared with their previous non-MA urine collection cycle (for patients with IMA or PMA). Many of these miRNAs have been previously associated with kidney function, and have roles in the pathophysiology of diabetes 23 , 24 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , ...…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that statins exhibit differential effects in CI-AKI prevention when given at equivalent lipid-lowering doses. These results must be confirmed by randomized controlled trials with larger sample sizes using more sensitive markers of renal parenchymal injury, such as neutrophil gelatinase-associated lipocalin or microRNAs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 levels have been observed to increase continuously in proliferating cells ( 12 , 25 ), starting at 24 h post injury ( 29 ). Therefore, its expression did not increase within 24 h reperfusion subsequent to 20 min of ischemia, or within 8 h of CM administration ( 13 , 30 ). It has been demonstrated that one-half of the amount of CM in the bloodstream may be eliminated quickly, in ~2 h ( 31 ).…”
Section: Discussionmentioning
confidence: 97%